Workplace Gender Pay Gaps: Does Gender Matter Less the Longer Employees Stay?. Issue 1 (February 2020) - Kronberg, Anne-Kathrin
Research indicates men often receive greater merit rewards than women for the same performance. It is unclear, however, whether gender differences in merit rewards narrow with increasing firm tenure or whether gender differences in merit-rewards stay constant across employees' firm-internal career. Using longitudinal personnel records of a private U.S. employer (2005–2014), the author finds no evidence for declining gender effects on pay when employees stay longer, not even among nonprofessionals where performance is easier to assess. Results contradict information-based theories and speak to status characteristics theory. Moreover, gender disparities are significant only when supervisors have discretion over merit increases.